AGE AND GENDER WITH DEGREE OF HYPERTENSION IN ADULTS AT THE CARDIOLOGY CLINIC OF GOTONG ROYONG HOSPITAL IN SURABAYA - Putu Raka Prema Aristian; Epriyanto Tri Darmadi; Maria Patricia Dian Putri (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Background : Hypertension is a condition that blood pressure in a person increases with systolic 140 mmHg and/or diastolic 90 mmHg, either based on clinical measurements or health care facilities. Hypertension is often called a